1986
DOI: 10.1104/pp.81.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Macrocyclic Diterpene Casbene in Castor Bean (Ricinus communis L.) Seedlings

Abstract: ABSTRACIFarnesyl transferase (farnesyl pyrophosphate: isopentenyl pyrophosphate farnesyl transferase; geranylgeranyl pyrophosphate synthetase) was purified at least 400-fold from extracts of castor bean (Ricinus communis L.) seedlings that were elicited by exposure for 10 h to Rhizopus stolonifer spores. The purified enzyme was free of isopentenyl pyrophosphate isomerase and phosphatase activities which interfere with prenyl transferase assays. The purified enzyme showed a broad optimum for farnesyl transfer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although significant cytosolic FPP synthase activity can be detected in homogenates of decapitated M. sexta larvae whose guts were removed, only small amounts of FPP formation are detected in corpora allata homogenates when conventional assay buffers (20-100 mM Tris-HCl or phosphate buffer, pH 7, 2-5 mM MgCl 2 , containing 0-10 mM KF to inhibit endogenous phosphatases) are used. Similar low levels of short-chain prenyl transferase activity have been noted in plants and bacteria and have been attributed to either enzyme lability or membrane association (Green et al, 1975;Takahashi and Ogura, 1981;Spurgeon et al, 1984;Sagami and Ogura, 1985;Dudley et al, 1986;Heide and Berger, 1989;Croteau and Purkett, 1989). Because activity in these cases was increased by the addition of glycerol and we decided to examine the effect of several additives on corpora allata prenyl transferase activity.…”
Section: Resultsmentioning
confidence: 65%
“…Although significant cytosolic FPP synthase activity can be detected in homogenates of decapitated M. sexta larvae whose guts were removed, only small amounts of FPP formation are detected in corpora allata homogenates when conventional assay buffers (20-100 mM Tris-HCl or phosphate buffer, pH 7, 2-5 mM MgCl 2 , containing 0-10 mM KF to inhibit endogenous phosphatases) are used. Similar low levels of short-chain prenyl transferase activity have been noted in plants and bacteria and have been attributed to either enzyme lability or membrane association (Green et al, 1975;Takahashi and Ogura, 1981;Spurgeon et al, 1984;Sagami and Ogura, 1985;Dudley et al, 1986;Heide and Berger, 1989;Croteau and Purkett, 1989). Because activity in these cases was increased by the addition of glycerol and we decided to examine the effect of several additives on corpora allata prenyl transferase activity.…”
Section: Resultsmentioning
confidence: 65%
“…The GGPPS is a homodimeric prenyl transferase occurred ubiquitously in plants, animals and bacteria [8]. Previous studies showed that heterologous expression of GGPPS gene in Escherichia coli or Saccharomyces cerevisiae resulted in the accumulation of diterpenes, including casbene [9]. This finding indicates that a large increase in GGPPS activity might correspond to the accumulation of diterpenes.…”
Section: Introductionmentioning
confidence: 80%
“…Meanwhile, at a concentration of more than 1 mM Mn 2+ are strongly inhibitors. [11] Another study mentioned that a high concentration of Mn 2+ disrupt the bond between the substrate with the enzyme. [12] The treatment was also carried out with n-etilmaeimid (NEM) on brownish callus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, NEM can inhibite IPP isomerase enzyme, geranil transferase, and farnesil transferase activity. [10,11] Since both compounds were found to have influence in the biosynthesis secondary metabolites through IPP and DMAPP pathway, they were chosen as inhibitor of phorbol esters. These toxic compounds belonging to diterpen were synthesized via IPP and DMAPP pathway.…”
Section: Discussionmentioning
confidence: 99%